Developing Ability to Collect Patterns Using Natural Material Media in Class IV Students - Mohammad Archi Maulyda; Muhammad Erfan (Jurnal Educatio FKIP UNMA, 2022)
This research is based on the results of observations and experiences of researchers, that cognitive ability in compiling patterns is still low. The use of natural material media will be more fun for children in compiling patterns, because natural material media are very interesting for children. Based on this background, the problems studied were formulated, namely: "Can using natural material media develop the ability to compose patterns in fourth grade students?". This study uses a Classroom Action Research (CAR) approach with a sample of fourth-grade students in an elementary school in the city of Mataram. This research was conducted in three cycles, using an assessment instrument in the form of sheets of the ability to compose patterns with natural materials media and teacher observation sheets. The results of this study, namely the media of natural materials proved successful and able to develop the ability to compose patterns in fourth-grade elementary school students. This can be seen from the results of data analysis on the use of natural media in the first cycle reaching 58.34%, the second cycle 70.84%, ​​and the third cycle 87.50%. Based on the results of the study, it can be concluded that the act of learning through the use of natural media can develop the ability to compose patterns in fourth-grade students in elementary schools.